ANALISIS MOTIVASI KERJA PERAWAT DI RSUD AMBARAWA KABUPATEN SEMARANG TAHUN 2017 - Ismal Wahyu; Septo Pawelas Arso; Eka Yunila Fatmasari (Jurnal Kesehatan Masyarakat (Undip), 2018)
Work motivation is an influental condition for generating, directing and treating behavior related to work environment. Generally, motivation appear because of  material, but in expectancy theory motivation is generated by hopes, value and result. Observational results showed that the nurse’s delay level was 10% with 30 minutes – 1 hour delay time, lack of appreciation, has not been awarded and the collected results was not as expected. Therefore, a comprehensive research was needed to describe the nurse work motivation level in Ambarawa Regional Public Hospital. This research used survey method with cross sectional approach. The samples were 69 nurses practitioners who met the inclusion criteria. The results showed that the mean nurse’s age was 31-40 years old for 34,8%, females for 82,6%, Diploma degree for 56,5%, government employees status for 66,7%, and work period of 1-10 years for 58%. The hope perception was low for 58%, value perception was low for 53,6%, result perception was low for 59,4%. Moreover, nurse motivation level in Ambarawa Regional Public Hospital was classified as low for 87,0% (60 people) with mean score of motivation of 2,69. Motivation score was obtained using total calculation of f(V1, x I) the result then V2 x E. Motivational factors were measured to get the rank of the total multiplication (V1 x I)/69. So obtained the level of motivational factors by the existence of health insurance, gain services, comfortness of the workplace, increased salary, and a fair treatment from the boss to the nurse during the work.